DNA-templated synthesis of biomimetic cell wall for nanoencapsulation and protection of mammalian cells - Peng Shi (Nature Portfolio, 2019)
The creation of protective barriers around cells is of interest for a range of applications. Here, the authors report on the creation of DNA templated alginate-polylysine biomimetic cell walls for encapsulating and shielding cells, demonstrating protection against physical assaults and immune reactions.